2018
DOI: 10.7717/peerj.4267
|View full text |Cite|
|
Sign up to set email alerts
|

Response of methane production via propionate oxidation to carboxylated multiwalled carbon nanotubes in paddy soil enrichments

Abstract: Carboxylated multiwalled carbon nanotubes (MWCNTs-COOH) have become a growing concern in terms of their fate and toxicity in aqueous environments. Methane (CH4) is a major product of organic matter degradation in waterlogged environments. In this study, we determined the effect of MWCNTs-COOH on the production of CH4 from propionate oxidation in paddy soil enrichments. The results showed that the methanogenesis from propionate degradation was accelerated in the presence of MWCNTs-COOH. In addition, the rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Mean CH 4 fluxes of the riparian zone from 2015 to 2016 in this study (0.47±1.53 mg•m -2 •h -1 ) were similar to values reported for other wetland catchments(0.0~2.22 mg•m -2 •h -1 ) (Badiou et al, 2011;Finocchiaro et al, 2014;Yang M et al, 2014).The production of CH 4 in various eco-systems is closely related to the anaerobic environment, which is beneficial to the methanogen metabolic activities Zhang et al, 2018). Soil water content, which affects the methane consuming capacity of methane-oxidizing bacteria by changing the transmission rate and the soil environmental condition (Koh et al, 2009), probably was a reason of the significant difference in the CH fluxes among the paddy fields, dry lands and grasslands.…”
Section: The Contribution Of Cultivation To Ghg Emissionssupporting
confidence: 88%
“…Mean CH 4 fluxes of the riparian zone from 2015 to 2016 in this study (0.47±1.53 mg•m -2 •h -1 ) were similar to values reported for other wetland catchments(0.0~2.22 mg•m -2 •h -1 ) (Badiou et al, 2011;Finocchiaro et al, 2014;Yang M et al, 2014).The production of CH 4 in various eco-systems is closely related to the anaerobic environment, which is beneficial to the methanogen metabolic activities Zhang et al, 2018). Soil water content, which affects the methane consuming capacity of methane-oxidizing bacteria by changing the transmission rate and the soil environmental condition (Koh et al, 2009), probably was a reason of the significant difference in the CH fluxes among the paddy fields, dry lands and grasslands.…”
Section: The Contribution Of Cultivation To Ghg Emissionssupporting
confidence: 88%
“…This research into the impact of carbon cloth on soil methane production is novel. Methanogenesis has been found to be stimulated by other conductive magnetite and carbon nanotube material (Kato et al, 2012;Yang et al, 2016;Zhang and Lu, 2016;Zhang et al, 2018;Zhuang et al, 2015). The promotion of CO 2 reduction by increased electron transfer is the key mechanism advocated by those studies.…”
Section: Discussionmentioning
confidence: 91%
“…Based on this, compared with artificial anaerobic fermentation system, strategies pertinent to use of conductive carbon materials in microbial methane production require clarification in a natural environment. Some studies showed that methanogenic process was also facilitated by electric syntrophy via magnetite (Kato et al, 2012;Xiao et al, 2018;Zhuang et al, 2015), biochar (Wang et al, 2017), and carbon nanotubes (Zhang and Lu, 2016;Zhang et al, 2018) in natural soil or sediments: however, little is known about the stimulation strategy of carbon cloth on methane production in natural environments.…”
mentioning
confidence: 99%
“…Mean CH 4 fluxes of the riparian zone from 2015 to 2016 in this study (0.47 ± 1.53 mg m −2 h −1 ) were similar to values reported for other wetland catchments (0.0∼2.22 mg m −2 h −1 ) (Badiou et al, 2011;Finocchiaro, Tangen & Gleason, 2014;Yang et al, 2014). The production of CH 4 in various eco-systems is closely related to the anaerobic environment, which is beneficial to the methanogen metabolic activities (Zhou et al, 2014;Zhang et al, 2018). Soil water content, which affects the methane consuming capacity of methaneoxidizing bacteria by changing the transmission rate and the soil environmental condition (Koh, Ochs & Yu, 2009), probably was a reason of the significant difference in the CH 4 fluxes among the paddy fields, dry lands and grasslands.…”
Section: The Contribution Of Cultivation To Ghg Emissionsmentioning
confidence: 99%